Implementasi Framework Scrum Pada Aplikasi Project Management PT. Rutan Berbasis Mobile - William Evan Budiawan; Yulia Yulia; Anita Nathania Purbowo (Jurnal Infra, 2022)
Project management is the process of planning and controlling an ongoing project. Nowadays, a lot of companies started to divert their current systems into digital formed systems, which can be accessed anywhere, everywhere. PT. Rutan as a company that prioritizes innovation, plans to digitalize the current existing project management system. Until now, PT. Rutan has no active management system that controls the performance of the company’s employees, and almost everything was done manually. In this research, a mobile application and a website was designed and developed to assist PT. Rutan in project management. The framework which will be implemented in the mobile application is the Scrum framework. The usage of the Scrum framework has been proven to improve task monitoring, task assignment, project scheduling, and evaluating the project. Based on tests conducted using a questionnaire at the Department of Information and Technology of PT. Rutan, the mobile application and website that have been developed have successfully helped in organizing, managing, and controlling project tasks. Overall, the mobile application and website created were also given a very good score by the Department of Information and Technology of PT. Rutan.